ASSESSING THE LEVEL OF POPULARITY OF EUROPEAN STAG TOURISM DESTINATIONS - Iwanicki, Grzegorz; Dłużewska, Anna; Smith Kay, Melanie (Quaestiones Geographicae, 2016)
The primary objective of this article is to determine the degree of popularity of stag tourism destinations in Europe. Research was based on the search engine method, involving an analysis of the highest positioned offers of travel agencies in the most commonly used search engines in Europe (Google, Bing, Yahoo). The analysis divided the studied cities into four categories in terms of popularity. Conducting the said analysis is strongly justified, because academic publications have so far not provided studies which have determined the degree of popularity of stag destinations on a continental scale.